(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In order to expand the range of measured physical quantities, it is proposed to record a series of holographic interferograms by modulating reference beams using matte scatterers. As a result, the measurement range increased 3-4 times.